Understanding resistance dynamics in pasang masda’s response to the public utility vehicle modernization program through Deline's double interact model - Escosio, Ohbee Christian Will G. (Animo Repository, 2024)
This thesis explores the intricate dynamics of resistance within Pasang Masda, a prominent transport cooperative, in response to the Public Utility Vehicle Modernization Program (PUVMP). Employing Deline's (2019) double interact model (DIM), the study aims to uncover how leaders, operators, and drivers within Pasang Masda construct and interpret resistance frames. Data was collected from interviews with 5 leaders and 30 members of Pasang Masda’s cooperatives: Malabon Jeepney Transport Service Cooperative (MAJETSCO) and Daanghari Modern Jeepney Transport Cooperative (DMJTCo.) The Grounded theory method was used for data analysis, involving open and axial coding of resistance interpretations gathered from the interview, wherein Deline’s (2019) resistance frames were incorporated. Findings revealed that Pasang Masda leaders and members used all resistance frames identified by Deline (2019), but there are significant differences in how it was used. Majority of participants utilized the Disagreeability Resistance Frames regarding financial, operational, and communication aspects of the program. A novel resistance frame was also discovered, deemed as “External Compliance Pressure '' which pertains to when members are perceived to comply despite not agreeing due to the mandatory nature of the program, to secure their livelihood. By addressing key research questions and objectives, this research contributes to the organizational communication literature, offering insights into the challenges of implementing change within a transport cooperative facing the demands of jeepney modernization. Keywords: Double Interact Model, Organizational Change, Change Implementation, Resistance to Organizational Change, Resistance Frames, Semi-structured Interview, Grounded Theory Analysis